Situación patrimonial de las cooperativas de ahorro y crédito del sector popular y solidario del segmento 1 periodo 2021. - Curipoma Cuzco, Karen Estefania (Universidad Técnica de Machala, 2022)
The present investigative work aims to demonstrate compliance with the legal requirement that the entities of the Ecuadorian National Financial System must maintain regarding the sufficiency of equity to face their operations and the risks that may arise, under the current regulations established in the Financial Monetary Organic Code. The objective of the research is to analyze the patrimonial situation of the savings and credit cooperatives of the popular and solidarity sector of segment 1 in the year 2021. For the development of the research, the methodology that will be applied will be documentary and bibliographic, where information will be taken from regulations in force for the year to be analyzed, reports submitted by regulatory entities, data provided by the Superintendence of Popular and Solidarity Economy (SEPS) and information published by the Association of Banks of Ecuador (ASOBANCA). For a better understanding, basic concepts that start from the most important will be analyzed to later proceed to the resolution of the practical case, where the interpretation of it will be indicated and detailed. The results are presented from the analysis of the indicator exposed in the research, clarifying the importance of savings and credit cooperatives in the development and macroeconomic growth of a country, as well as compliance with them by maintaining sufficient equity solvency despite of the adversities that the different financial institutions have had to go through in recent years, which has contributed to its constant evolution and adaptation when viewed from a positive perspective.
El presente trabajo investigativo pretende demostrar el cumplimiento del requerimiento legal que deben mantener las entidades del Sistema Financiero Nacional ecuatoriano respecto a la suficiencia patrimonial para ser frente a las operaciones de las mismas y los riesgos que se puedan originar, bajo la normativa vigente establecida en el Código Orgánico Monetario Financiero. La investigación tiene como objetivo analizar la situación patrimonial de las cooperativas de ahorro y crédito del sector popular y solidario del segmento 1 en el año 2021. Para el desarrollo de la investigación la metodología que se aplicará será documental y bibliográfica, donde se tomará información de normativas vigentes del año a analizar, informes presentados por entidades reguladoras, datos proporcionados de la superintendencia de economía popular y solidaria (SEPS) e información publicada por la Asociación de Bancos de Ecuador (ASOBANCA). Para un mejor entendimiento se analizarán conceptos básicos que inician desde lo más importante para posteriormente proceder a la resolución del caso práctico, donde se indicará y detallará la interpretación del mismo. Los resultados se presentan a partir del análisis del indicador expuesto en la investigación aclarando la importancia de las cooperativas de ahorro y crédito en el desarrollo y crecimiento macroeconómico de un país, así como también el cumplimiento de las mismas al mantener la suficiente solvencia patrimonial a pesar de las adversidades que las distintas instituciones financieras han tenido que pasar durante los últimos años, lo que ha contribuido a su constante evolución y adaptación al observar desde una perspectiva positiva.
Keywords: COOPERATIVAS; SUFICIENCIA; PATRIMONIO; POPULAR